Function of Ubiquinone in Electron Transport from Reduced Nicotinamide Adenine Dinucleotide to Nitrate and Oxygen in Aerobacter aerogenes - Knook, D. L. (1971)
The possible role of quinones in the electron transport system of Aerobacter aerogenes was investigated. The only quinone found in measurable amounts in bacteria grown in minimal media under both aerobic and anaerobic conditions was ubiquinone-8. Membrane-bound ubiquinone-8 could be removed by extraction with pentane, or destroyed by ultraviolet irradiation, with a concomitant loss of both reduced nicotinamide adenine dinucleotide (NADH) oxidase and NADH-linked respiratory nitrate reductase activity. In the extracted membrane preparations, these enzymatic activities could be restored, both to the same degree, by incorporation of ubiquinone-6, -8, or -10, but not by incorporation of menaquinones. The NADH oxidation and the nitrate reduction were sensitive to the respiratory inhibitors dicoumarol, lapachol, and cyanide. The results obtained indicate that ubiquinone-8 mediates the electron transport between NADH and oxygen as well as between NADH and nitrate. Branching of the electron transport chain to oxygen and nitrate occurs after an initial common pathway.